Does GCG Structure Create Value? Evidence from Indonesia’s Food and Beverage Sector - Aisyah Kartika Dewi; Syarifah Ratih Kartika Sari; Arini Wildaniyati (Pattimura Proceeding, 2026)
This study aims to examine the effect of Good Corporate Governance (GCG) mechanisms and profitability on company value, with GCG as a structurally measured governance mechanism and profitability as the main indicator of financial performance. Unlike the normative approach, which assumes that GCG structures automatically increase company value, this study treats GCG as a formal mechanism whose effectiveness needs to be tested empirically. The research sample consists of companies in the food and beverage sub-sector listed on the IDX during the 2022–2024 period, resulting in 222 observations. Company value is proxied using Tobin's Q, while GCG mechanisms are measured through the number of board members, independent commissioners, directors, and audit committees. Profitability is proxied by Return on Assets (ROA). The analysis was conducted using multiple linear regression to test the associative relationship. The results show that profitability has a significant positive effect on company value, while most structural GCG mechanisms do not show a consistent positive effect, and some even show a negative relationship. These findings indicate that the formal structure of GCG has limitations in explaining company value, and that the market responds more to financial performance than to normative assumptions about the effectiveness of governance